Impact of Reduced Preincision Antibiotic Infusion Time on Surgical Site Infection Rates: A Retrospective Cohort Study. Issue 4 (April 2020) - Malhotra, Neil R.; Piazza, Matthew; Demoor, Rebecca; McClintock, Scott D.; Hamilton, Keith; Sharma, Nikhil; Osiemo, Benjamin; Berger, Ian; Hossain, Erik; Borovskiy, Yuliya; Maloney, Eileen; Smith, Lachlan J.; et al.
Abstract : Objective: Our objective was to determine the impact of total preincision infusion time on surgical site infections (SSIs) and establish an optimal time threshold for subsequent prospective study. Background: SSIs remain a major cause of morbidity. Although regulated, the total time of infusion of preincision antibiotics varies widely. Impact of infusion time on SSI risk is poorly understood. Methods: All consecutive patients (n = 46, 791) undergoing inpatient surgical intervention were retrospectively enrolled (2014–2015) and monitored for 1 year. Primary outcomes : the presence of SSI infection as predicted by reduced preoperative antibiotic infusion time. Secondary outcomes : preintervention compliance, the impact of a quality improvement algorithm to optimize infusion time compliance. Multivariate logistic regression of the retrospective cohort demonstrated predictors of infection. Receiver-operating characteristic analysis demonstrated the timing threshold predictive of infection. Cost impact of avoidable infections was analyzed. Results: Only 36.1% of patients received preincision infusion of vancomycin in compliance with national and institutional standards (60–120 min). Cephalosporin infusion times were 53 times more likely to be compliant [odds ratio (OR) 53.33, P < 0.001]. Vancomycin infusion times that were not compliant with national standards (less than standard 60–120 min) did not predict infection. However, significantly noncompliant, reduced preincision infusion time, significantly predicted SSI (<24.6 min infusion, AUC = 0.762). Vancomycin infusion, initiated too close to surgical incision, predicted increased SSI (OR = 4.281, P < 0.001). Implementation of an algorithm to improve infusion time, but not powered to demonstrate infection /reduction, improved vancomycin infusion start time (257% improvement, P < 0.001) and eliminated high-risk infusions (sub-24.6 min). Conclusions: Initially, vancomycin infusion rarely met national guidelines; however, minimal compliance breach was not associated with SSI implications. The retrospective data here suggest a critical infusion time for infection reduction (24.6 min before incision). Prospective implementation of an algorithm led to 100% compliance. These data suggest that vancomycin administration timing should be studied prospectively. Abstract : Supplemental Digital Content is available in the text